ImmunoglobuliNin the Treatment of Encephalitis (IgNiTE): protocol for a multicentre randomised controlled trial. Issue 11 (3rd November 2016) - Iro, M A; Sadarangani, M; Absoud, M; Chong, W K; Clark, C A; Easton, A; Gray, V; Kneen, R; Lim, M; Pike, M; Solomon, T; Vincent, A; et al.
Abstract : Introduction: Infectious and immune-mediated encephalitides are important but under-recognised causes of morbidity and mortality in childhood, with a 7% death rate and up to 50% morbidity after prolonged follow-up. There is a theoretical basis for ameliorating the immune response with intravenous immunoglobulin (IVIG), which is supported by empirical evidence of a beneficial response following its use in the treatment of viral and autoimmune encephalitis. In immune-mediated encephalitis, IVIG is often used after a delay (by weeks in some cases), while diagnosis is confirmed. Wider use of IVIG in infectious encephalitis and earlier use in immune-mediated encephalitis could improve outcomes for these conditions. We describe the protocol for the first ever randomised control trial of IVIG treatment for children with all-cause encephalitis. Methods and analysis: 308 children (6 months to 16 years) with a diagnosis of acute/subacute encephalitis will be recruited in ∼30 UK hospitals and randomised to receive 2 doses (1 g/kg/dose) of either IVIG or matching placebo, in addition to standard treatment. Recruitment will be over a 42-month period and follow-up of each participant will be for 12 months post randomisation. The primary outcome is 'good recovery' (score of 2 or lower on the Glasgow Outcome Score Extended—paediatric version), at 12 months after randomisation. Additional secondary neurological measures will be collected at 4–6 weeks after discharge from acute care and at 6 and 12 months after randomisation. Safety, radiological, other autoimmune and tertiary outcomes will also be assessed. Ethics and dissemination: This trial has been approved by the UK National Research Ethics committee (South Central—Oxford A; REC 14/SC/1416). Current protocol: V4.0 (10/03/2016). The findings will be presented at national and international meetings and conferences and published in peer-reviewed journals. Trial registration numbers: NCT02308982, EudraCT201400299735 and ISRCTN15791925 ; Pre-results.